Splines in Periodic Time-Domain Circuit Analysis - Bartkevicius, S. (Elektronika ir Elektrotechnika, 1998)
A method of calculation of periodic solutions of circuit equations using splines is proposed. An approximation with filtering properties eliminating oscillations on discretization frequency is discussed.